PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF MENGGUNAKAN APLIKASI CAPCUT BERBASIS MODEL DISCOVERY LEARNING PADA PEMBELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Dina Lestari Sitompul; Yeni Erita; Arwin; Masniladevi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is one of the important factors in improving the quality of human resources. To achieve educational goals, an innovative learning process supported by technology as an engaging and innovative learning medium is required. However, based on the results of the preliminary observation, the utilization of technology in the learning process of fifth-grade elementary school students has not been optimized. As a result, the learning process is still dominated by conventional teaching methods and does not actively engage students. Therefore, this study aimed to develop interactive learning video media using the Capcut application based on the Discovery Learning model for IPAS learning in Grade V of elementary school that is valid, practical, and effective. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The developed product was validated by material experts, media experts, and language experts using validation questionnaires. The practicality of the media was assessed through teacher and student response questionnaires, while its effectiveness was measured based on students' learning outcomes. The product was tested at SDN 01 Indarung as the pilot school and implemented at SDN 11 Indarung and SDN 20 Indarung. The results showed that the developed interactive learning video media achieved a validity score of 83%, categorized as very valid. The practicality score was 94.44% based on teachers' responses and 95.53% based on students' responses, both categorized as very practical. In addition, the effectiveness score reached 79.36%, categorized as effective. Therefore, the interactive learning video media using the Capcut application based on the Discovery Learning model for IPAS learning in Grade V of elementary school was declared valid, practical, and effective for use in the learning process.